Provable data possession scheme based on public verification and private verification - Junfeng TIAN; Mengjia CHAI; Liuling QI (Tongxin xuebao)
More and more users choose to transfer their applications and data into the cloud.Data security is a key issue for cloud storage systems.To ensure the integrity and validity of the data stored in the cloud,provable data possession (PDP) scheme is particularly important.In order to verify whether the cloud storage service provider had stored the data of the user completely,a scheme on the basis of NRPDP (non-repudiable PDP) was improved and extended,and a data retention scheme based on public authentication and private authentication was proposed.The scheme can verify the trustworthiness of the service provider and the user in the cloud storage at the same time,which satisfies the non-repudiation of the verification.The theory proves the non-repudiation of the proposed scheme.The experiment proves that the efficiency of each stage is better than that of the existing single public verification method or private authentication method.